Alteration of organic matter and copper mineralization in the Midcontinent Rift, USA - Schultz, Max, author; Ridley, John, advisor; Sutton, Sally, committee member; Kennan, John, committee member (Colorado State University. Libraries, 2017)
To view the abstract, please see the full text of the document.